Education law and the private schools : a practical guide for educational leaders and policymakers - Sarmiento, Ulpiano P. ([Manila] : Ulpiano P. Sarmiento, 2006)
This new book provides school administrators a treasury of materials on education law that are handy for consultation and information.
Chapter 1. General Provisions -- Chapter 2. The Education System -- Chapter 3. Education Institutions -- Chapter 4. Terms and conditions of Employment -- Chapter 5. School Finance and Assistance -- Appendices.
Keywords: PRIVATE SCHOOLS -- LAW AND LEGISLATION -- PHILIPPINES